Intrarenal Color Doppler Ultrasonography in the Diagnosis of Accessory Renal Artery Stenosis - Rauniyar, RK; Srivastava, DN; Bal, CS; Dash, SC; Berry, M (Nepalese Journal of Radiology, 2013)
Conventional color Doppler ultrasonography of main renal artery is a valuable non invasive tool in screening and diagnosing patients with renal artery stenosis. However, this technique suffer a set back from many limitations. Color Doppler ultrasonography examination of intrarenal branch arteries using the parameters like, acceleration time, acceleration time ratio, and acceleration index with additional sampling from upper and lower pole of kidney has shown good results in diagnosis of renal artery stenosis. We successfully diagnosed accessory renal artery stenosis in two patients using intrarenal Doppler technique. We conclude, intra renal Color Doppler ultrasonography with additional sampling from upper and lower pole is most accurate method for diagnosis of significant RAS including accessory RAS. Nepalese Journal of Radiology; Vol. 2; Issue 2; July-Dec. 2012; 59-64 DOI: http://dx.doi.org/10.3126/njr.v2i2.7687